Monoamine Oxidase B Prompts Mitochondrial and Cardiac Dysfunction in Pressure Overloaded Hearts - Kaludercic, Nina (Mary Ann Liebert, Inc., 2014)
Aims: Monoamine oxidases (MAOs) are mitochondrial flavoenzymes responsible for neurotransmitter and biogenic amines catabolism. MAO-A contributes to heart failure progression via enhanced norepinephrine catabolism and oxidative stress. The potential pathogenetic role of the isoenzyme MAO-B in cardiac diseases is currently unknown. Moreover, it is has not been determined yet whether MAO activation can directly affect mitochondrial function. Results: In wild type mice, pressure overload induced by transverse aortic constriction (TAC) resulted in enhanced dopamine catabolism, left ventricular (LV) remodeling, and dysfunction. Conversely, mice lacking MAO-B (MAO-B(−/−)) subjected to TAC maintained concentric hypertrophy accompanied by extracellular signal regulated kinase (ERK)1/2 activation, and preserved LV function, both at early (3 weeks) and late stages (9 weeks). Enhanced MAO activation triggered oxidative stress, and dropped mitochondrial membrane potential in the presence of ATP synthase inhibitor oligomycin both in neonatal and adult cardiomyocytes. The MAO-B inhibitor pargyline completely offset this change, suggesting that MAO activation induces a latent mitochondrial dysfunction, causing these organelles to hydrolyze ATP. Moreover, MAO-dependent aldehyde formation due to inhibition of aldehyde dehydrogenase 2 activity also contributed to alter mitochondrial bioenergetics. Innovation: Our study unravels a novel role for MAO-B in the pathogenesis of heart failure, showing that both MAO-driven reactive oxygen species production and impaired aldehyde metabolism affect mitochondrial function. Conclusion: Under conditions of chronic hemodynamic stress, enhanced MAO-B activity is a major determinant of cardiac structural and functional disarrangement. Both increased oxidative stress and the accumulation of aldehyde intermediates are likely liable for these adverse morphological and mechanical changes by directly targeting mitochondria. Antioxid. Redox Signal. 20, 267–280.